The Use of Culturally Responsive Teaching-Based Magic Learning Boxes on the Learning Interests of Grade V Students - Sakdiyah, Siti Halimatus; Herlina, Adisty Revi; Susanti, Tina (Kognisi : Jurnal Penelitian Pendidikan Sekolah Dasar, 2025)
This study aims to improve the learning outcomes of Natural and Social Sciences among grade IV C students of Public Elementary School 1 Bakalan Krajan Malang through the application of the Discovery Learning model assisted by electronic student worksheets (e-learning worksheets). The background of this study lies in the low learning outcomes and limited student engagement in Natural and Social Sciences learning, which are partly caused by conventional instructional methods and the lack of interactive digital learning materials. This classroom action research was implemented in two cycles following the Kemmis and McTaggart model, consisting of the stages of planning, implementation, observation, and reflection. In the first cycle, learning was carried out using the Discovery Learning model without integrating electronic worksheets, while in the second cycle, the process was supplemented with interactive electronic worksheets designed to guide students in discovery activities, problem-solving, and critical thinking tasks. The subjects of this study were 28 students of grade IV C. Data were collected through learning outcome evaluation tests administered at the end of each cycle. The findings showed a significant improvement in learning mastery, increasing from 58 percent in the first cycle to 89 percent in the second cycle, reflecting a 31 percent enhancement. These results demonstrate that the application of the Discovery Learning model assisted by electronic worksheets is effective not only in improving students’ learning outcomes in Natural and Social Sciences but also in fostering active participation, engagement, and motivation throughout the learning process.